The use of open source educational software (OER) in the development of electronic performance competencies for students with visual disabilities in Al-Nour School in Assiut Governorate - Tolba, Reham Hassan Mohamed (Journal of Educational and Psychological Sciences, 2018)
The aim of this research is to reveal the use of OER software in the development of electronic performance competencies for people with visual disabilities. The study used the experimental method. The tool was implemented in a program implemented by NVDA as a model for OER software for the development of e-learning competencies in a sample of 12 students with visual disabilities in Al-Nour School in Assiut Governorate. They were divided into two experimental groups: And the second experimental group of 6 students was taught using tactility. The research tools were in a note card to measure their ability to perform the e-competencies. The results of the research concluded that (Α = 0.05) between the mean scores of the research sample in the tribal and remote applications on a note card in favor of the post application. The first experimental group obtained a (tailed test) at a mean level equal to (027) (0.05) in favor of the post-application, and the second experimental group was in the post-test; the level of significance is equal to (028.) which is less than (0.05). This indicates that there are differences in the performance of students with visual disabilities before and after the use of the program, The results demonstrated the effectiveness of open source educational software using hearing aids. The first group obtained a (tailed test) at the level of significance (052.) against the level of significance (062.) for the second group studied using tactility. In light of these findings, a number of recommendations were made, focusing on the need to guide the use of open source educational software in support of the various learning processes for people with visual disabilities, and to utilize their potential to serve the educational process and integrate it into the classrooms. And rely on technological applications to enhance learning environments and change the traditional patterns that students are accustomed to.
Keywords: open source educational software; performance electronic competencies; visual impairment